2001
DOI: 10.1002/ajh.10008
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of sinus histiocytosis with massive lymphadenopathy (rosai‐dorfman disease): Report of a case and literature review

Abstract: Sinus histiocytosis with massive lymphadenopathy (SHML) is a rare disorder of unknown etiology, usually associated with lymph node enlargement in various super®cial or deep sites. It usually shows a prolonged clinical course with occasional exacerbation and remission phases. We describe the long-term follow-up of a case of SHML that showed typical clinical features and in which various therapeutic strategies were attempted. Chemotherapy and a-interferon (IFN) were ineffective; surgery was ultimately required w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
286
1
20

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 365 publications
(309 citation statements)
references
References 15 publications
(13 reference statements)
2
286
1
20
Order By: Relevance
“…Rosai-Dorfman disease, also known as sinus histiocytosis with massive lymphadenopathy, is a rare disease characterised by (mostly cervical) lymph node enlargement and fever, with a distinct cellular pattern of the lymph nodes [1]. The histopathological findings are massive sinus infiltration with histiocytes that show a large amount of cytoplasm in which lymphocytes are engulfed (emperipolesis; Rosai-Dorfman cells) that show immunohistochemical staining for S-100 protein without CD1a expression.…”
Section: To the Editorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rosai-Dorfman disease, also known as sinus histiocytosis with massive lymphadenopathy, is a rare disease characterised by (mostly cervical) lymph node enlargement and fever, with a distinct cellular pattern of the lymph nodes [1]. The histopathological findings are massive sinus infiltration with histiocytes that show a large amount of cytoplasm in which lymphocytes are engulfed (emperipolesis; Rosai-Dorfman cells) that show immunohistochemical staining for S-100 protein without CD1a expression.…”
Section: To the Editorsmentioning
confidence: 99%
“…In the majority of cases, however, the disease is self-limiting. Most patients do not require treatment with steroids [1].…”
Section: To the Editorsmentioning
confidence: 99%
See 2 more Smart Citations
“…RDD is generally self-limited with spontaneous resolution; however, it may have a prolonged course with remission, exacerbation, and even death [3,5]. After reviewing treatments, Pulsoni et al suggested observation without treatment is advisable except when compression or other clinical signs indicate surgical debulking [6]. This patient was successfully treated by curettage and bone grafting.…”
mentioning
confidence: 99%